The Effect of Feedback and Kinesio Taping on the Correction of Faulty Movement Patterns in Athletes With Lower Limb Injuries - Mohadeseh Ashrafizadeh; Hassan Daneshmandi; Parisa Sedaghati (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims This study addresses only those interventions, such as feedback and kinesio taping, that affect lower limb function in athletes with impaired lower limb movement patterns.Methods This research is a systematic review study that examined all published articles in English about the effect of feedback and kinesio taping on correcting defective movement patterns and reducing injury risk factors. The current study was conducted by searching foreign databases such as Google Scholar, PubMed, and ScienceDirect and domestic databases, including Magiran and Irandoc with the keywords of "videotape augmented feedback," "taping," "kinesio taping," and "lower extremity" from January 2000 to January 2021.Results After reviewing the full texts of 45 articles, 24 articles were finally selected according to the purpose of the research. Of 24 articles, 20 were interventional studies, 1 was a systematic review, 1 was a meta-analysis, and 2 were meta-analysis and systematic reviews. In all studies, feedback training methods positively affected lower limb biomechanics, and tipping methods improved pain.Conclusion After comparing the effects of feedback and kinesio taping interventions in the studied studies, it can be concluded that feedback is better than kinesio taping taping in improving kinetic and kinematic variables in people with lower limb movement pattern defects.